Methylene blue-induced neuronal protective mechanism against hypoxia-reoxygenation stress. (20th August 2015) - Ryou, M.-G.; Choudhury, G.R.; Li, W.; Winters, A.; Yuan, F.; Liu, R.; Yang, S.-H.
Highlights: MB stabilizes hypoxia-inducible factor-1α. MB increased ATP production after OGD-reoxygenation stress. MB-induced HIF-1α stabilization is associated with increased glucose metabolism. MB produces favorable intracellular environment for aerobic glycolysis. Abstract: Brain ischemia and reperfusion (I/R) injury occurs in various pathological conditions, but there is no effective treatment currently available in clinical practice. Methylene blue (MB) is a century-old drug with a newly discovered protective function in the ischemic stroke model. In the current investigation we studied the MB-induced neuroprotective mechanism focusing on stabilization and activation of hypoxia-inducible factor-1α (HIF-1α) in an in vitro oxygen and glucose deprivation (OGD)-reoxygenation model. Methods: HT22 cells were exposed to OGD (0.1% O2, 6 h) and reoxygenation (21% O2, 24 h). Cell viability was determined with the calcein AM assay. The dynamic change of intracellular O2 concentration was monitored by fluorescence lifetime imaging microscopy (FLTIM). Glucose uptake was quantified using the 2-[N-(7-Nitrobenz-2-Oxa-1, 3-Diazol-4-yl)Amino]-2-Deoxy-d -Glucose (2-NBDG) assay. ATP concentration and glycolytic enzyme activity were examined by spectrophotometry. Protein content changes were measured by immunoblot: HIF-1α, prolyl hydroxylase 2 (PHD2), erythropoietin (EPO), Akt, mTOR, and PIP5K. The contribution of HIF-1α activation in the MB-induced neuroprotective mechanism was confirmed by blocking HIF-1α activation with 2-methoxyestradiol-2 (2-MeOE2 ) and by transiently transfecting constitutively active HIF-1α. Results: MB increases cell viability by about 50% vs. OGD control. Compared to the corresponding control, MB increases intracellular O2 concentration and glucose uptake as well as the activities of hexokinase and G-6-PDH, and ATP concentration. MB activates the EPO signaling pathway with a corresponding increase in HIF-1α. Phosphorylation of Akt was significantly increased with MB treatment followed by activation of the mTOR pathway. Importantly, we observed, MB increased nuclear translocation of HIF-1α vs. control (about three folds), which was shown by a ratio of nuclear:cytoplasmic HIF-1α protein content. Conclusion: We conclude that MB protects the hippocampus-derived neuronal cells against OGD-reoxygenation injury by enhancing energy metabolism and increasing HIF-1α protein content accompanied by an activation of the EPO signaling pathway.